2015
DOI: 10.1128/jvi.00362-15
|View full text |Cite
|
Sign up to set email alerts
|

Increased Infectivity of Anchorless Mouse Scrapie Prions in Transgenic Mice Overexpressing Human Prion Protein

Abstract: Prion protein (PrP) is found in all mammals, mostly as a glycoprotein anchored to the plasma membrane by a C-terminal glycosylphosphatidylinositol (GPI) linkage. Following prion infection, host protease-sensitive prion protein (PrPsen or PrPC) is converted into an abnormal, disease-associated, protease-resistant form (PrPres). Biochemical characteristics, such as the PrP amino acid sequence, and posttranslational modifications, such as glycosylation and GPI anchoring, can affect the transmissibility of prions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…Prion aggregates accumulate during the conversion of the cellular prion protein, PrP C , into a β-sheet rich multimer known as PrP Sc (12,13). Although the PrP Sc structure has not yet been solved, several lines of evidence suggest that PrP posttranslational modifications (PTMs), a glycophosphatidylinositol (GPI) anchor and 2 N-linked glycans (14)(15)(16)(17)(18), impact the prion conformation (19)(20)(21), species barriers (22,23), and disease progression (24,25). Previous studies have demonstrated that PrP Sc maintains the sialylated glycans (α2,6-linked) (17,26) and that sialylation influences prion conversion and intracellular trafficking (27)(28)(29)(30)(31), yet how these bulky, anionic glycans modify prion assembly and the disease phenotype remains unresolved (32).…”
Section: Introductionmentioning
confidence: 99%
“…Prion aggregates accumulate during the conversion of the cellular prion protein, PrP C , into a β-sheet rich multimer known as PrP Sc (12,13). Although the PrP Sc structure has not yet been solved, several lines of evidence suggest that PrP posttranslational modifications (PTMs), a glycophosphatidylinositol (GPI) anchor and 2 N-linked glycans (14)(15)(16)(17)(18), impact the prion conformation (19)(20)(21), species barriers (22,23), and disease progression (24,25). Previous studies have demonstrated that PrP Sc maintains the sialylated glycans (α2,6-linked) (17,26) and that sialylation influences prion conversion and intracellular trafficking (27)(28)(29)(30)(31), yet how these bulky, anionic glycans modify prion assembly and the disease phenotype remains unresolved (32).…”
Section: Introductionmentioning
confidence: 99%
“…The zoonotic transmission of prion disease from animals to humans appears to vary with different species and prion agents. For example, in spite of likely exposures over the last 200 years, there is little evidence of transmission of scrapie from sheep to humans (5)(6)(7)(8). However, there is strong evidence for the transmission of bovine spongiform encephalopathy (BSE) from cattle to humans albeit at a very low frequency (9)(10)(11).…”
mentioning
confidence: 99%
“…Generation of prions seems to depend on more than just formation of PrP Sc and likely requires its assembly into unique structures. 99 A recent study described higher infectivity upon prion-challenge in mice expressing anchorless PrP C compared to wild type mice 106. However, since in this study the effect was only seen in recipient mice with dramatic overexpression of PrP C , results cannot be compared to our study where physiological shedding of PrP C is only abolished in a small subset of total brain cells 39.…”
mentioning
confidence: 56%